Utilising 'modern slave' narratives in social policy research. (February 2020) - Phillips, Coretta
Modern slavery has received somewhat limited attention in social policy. Partially responding to this gap, while acknowledging the contested nature of the term 'modern slavery', this article makes the case for the primary and secondary analysis of 'slave narratives' which provide experiential and agential accounts by those directly harmed by forced labour, coerced sex work and other forms of exploitation. Analysis of a narrative interview with Sean, a (citizen-)victim of forced labour proved under s.71 of the Coroners and Justice Act 2009, demonstrates the multifaceted nature of labour exploitation and its multiple, severe and long-lasting harms. That the form and structure of Sean's narrative of forced labour resembles those used in the abolitionist cause against antebellum slavery points to a certain timeless essence to forced labour exploitation. The article concludes with implications for intervention.